Pengaruh Hari Perdagangan Terhadap Return Saham Pada Bursa Efek Indonesia - Jefry Ardhian; Ichwan Marisan (Jurnal Rekognisi Akuntansi, 2017)
This study aims to examine the effect of trading days on stock returns on the LQ45 stock index listed on the Indonesia Stock Exchange and to examine the effect of trading days on abnormal stock returns on the LQ45 stock index listed on the Indonesia Stock Exchange. Trading days in this study include Monday, Tuesday, Wednesday, Thursday, and Friday. The population in this study is LQ45 shares listed on the Indonesia Stock Exchange. Samples were taken by purposive sampling method. The sample consisted of 243 days from 29 company stocks included in LQ45 during the research year February 2015 to January 2016. Testing the effect of trading days on stock returns was carried out by testing the regression coefficient of the trading day variable (Monday, Tuesday, Wednesday, Thursday, Friday) in regression model which is treated as a dummy variable by using multiple linear regression. The results of data analysis show that trading day has a significant effect partially on stock returns but does not have a significant effect on LQ45 stock returns simultaneously. Trading days have a significant partial effect on abnormal returns only on Tuesdays and Wednesdays but have a significant effect jointly on the LQ45 stock index for the research year 2015 to 2016